Animal feeding and management strategies in the commercial dairy farms - TIWARI, RUPASI; SHARMA, M C; SINGH, B P (The Indian Journal of Animal Sciences, 2011)
The study revealed a very poor calf and heifers feeding and management scenario in the commercial dairies. The shed management and breeding management was also very poor indicating that the commercial dairy owners use the dairy animals as a milking machine and discard the animals as soon as the milk production reduces. Therefore a lot of attention needs to be paid to the feeding and management pattern in the commercial dairies with special emphasis on the calf and heifer feeding and management. Â